2021
DOI: 10.7554/elife.61037
|View full text |Cite
|
Sign up to set email alerts
|

A flagellate-to-amoeboid switch in the closest living relatives of animals

Abstract: Amoeboid cells are fundamental to animal biology and broadly distributed across animal diversity, but their evolutionary origin is unclear. The closest living relatives of animals, the choanoflagellates, display a polarized cell architecture (with an apical flagellum encircled by microvilli) that closely resembles that of epithelial cells and suggests homology, but this architecture differs strikingly from the deformable phenotype of animal amoeboid cells. Here, we show that choanoflagellates subjected to conf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
3

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 118 publications
(157 reference statements)
0
48
0
Order By: Relevance
“…We hypothesise that the ability of sponge cells to quickly and effectively transdifferentiate is a trait inherited from pre-metazoan ancestors, which were capable of temporal cell differentiation [47,48,49]. This feature remains evident in extant animal relatives, including choanoflagellates [52]. However, while a comprehensive understanding of the cellular processes in sponge wound healing has been developed, the underlying genetic basis of this process remains largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesise that the ability of sponge cells to quickly and effectively transdifferentiate is a trait inherited from pre-metazoan ancestors, which were capable of temporal cell differentiation [47,48,49]. This feature remains evident in extant animal relatives, including choanoflagellates [52]. However, while a comprehensive understanding of the cellular processes in sponge wound healing has been developed, the underlying genetic basis of this process remains largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of fluorescent markers brought the cellular architecture of S. rosetta into living color in a way not possible previously (Figure 3D). The ability to express and perform live imaging of fluorescently tagged proteins also helped to validate the mapping of the jumble and couscous glycosyltransferases (Wetzel et al, 2018), revealed that septins localize to the basal pole of S. rosetta cells (Booth et al, 2018), and revealed the cytoskeletal dynamics that accompany the transition from flagellated swimming cells to crawling amoeboid cells upon confinement (Brunet et al, 2021). In addition, this protocol served as the foundation for transfection of the choanoflagellate Monosiga brevicollis (Woznica et al, 2021).…”
Section: Gene Delivery and Genome Editing In S Rosettamentioning
confidence: 99%
“…Engineering larger insertions, which will likely integrate into the genome with even lower frequencies, will require modifications to improve gene delivery, to increase integration frequencies, and/or to select for stable transgenes. A puromycin resistance gene has already been used for the selection of transgenic cassettes (Wetzel et al, 2018;Brunet et al, 2021;Woznica et al, 2021), but puromycin also affects the feeder bacteria that support choanoflagellate growth, leading to variable selection conditions. The development of more selectable markers that confer resistance to drugs that selectively target eukaryotes would help advance genetics in choanoflagellates and other heterotrophic organisms that require bacterial feeding.…”
Section: Gene Delivery and Genome Editing In S Rosettamentioning
confidence: 99%
“…Choanoflagellates have already served as powerful models for studying the origin of animal multicellularity and cell differentiation ( Levin et al, 2014 ; Alegado et al, 2012 ; Brunet et al, 2021 ; Dayel et al, 2011 ; Woznica et al, 2017 ; Brunet et al, 2019 ; Laundon et al, 2019 ) and are ideally positioned to yield insights into the evolution of animal immune pathways. Therefore, we sought to establish the choanoflagellate Monosiga brevicollis as a model for studying pathogen recognition and immune responses.…”
Section: Introductionmentioning
confidence: 99%